Case-Based Method for Enhancing Critical Thinking in English Debate Courses - Al Firdaus, Moch. Malik (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
This study investigates the challenges faced by students in expressing critical thinking and evaluates the implementation of the Case-Based Method in an English Debate and Critical Thinking (EDCT) course. Using a qualitative research design, data were collected from 35 undergraduate students through classroom observations, weekly reflections, and instructor interviews. The study identifies three primary challenges: a lack of understanding of debate fundamentals, insufficient critical thinking practice due to large class sizes, and limited knowledge of current issues, all of which hindered students’ ability to construct and articulate arguments effectively. To address these challenges, the study introduces the IDR (Introducing, Debating, Reviewing) framework. In the "Introducing" phase, students are given a preview of topics and motions, enhancing preparation and engagement. The "Debating" phase employs the British Parliamentary format with randomized roles, encouraging critical analysis from multiple perspectives and fostering adaptability. The "Reviewing" phase emphasizes peer feedback and collaborative learning, allowing students to refine their argumentation skills and deepen their understanding of the issues. The findings demonstrate the effectiveness of the Case-Based Method in improving students’ critical thinking and debate performance. It promotes active learning, enhances engagement, and develops essential analytical and communication skills. The study highlights the importance of integrating real-world issues and interactive practices into large classroom settings to overcome existing challenges. This research provides practical implications for educators seeking to implement effective pedagogical strategies in debate and critical thinking courses.